The Singing Poets – The Influence of Folksongs on Modern Arab Poets in the First Half of the Twentieth Century - khoury, jeries (International Journal of Language and Literary Studies, 2021)
Twentieth-century Arab poets undertook a search for alternative means of poetic expression that went beyond experimentation at the stylistic and formal level. The result was a violent rebellion against the traditional qa??da form in the mid-1940s, an urgent striving for freedom and breaking free from accepted forms. One of the rebellion’s manifestations consisted of a renewed interest in folklore, especially folksongs, as a source of inspiration. Early on, folksongs became a fundamental pillar of Arab Modernism; most of the poets of the first half of the twentieth century were, in fact, affected to differing degrees by the folksong style. Ultimately the present study shows that folk literature in general, and folksongs in particular, are a critical source of inspiration for Arab poets, one which has enabled them to forge a link between their art and their public.